Exploring The Cognition and Attitude of Vocational High School Students Towards Autonomous Vehicles - Li, Wei; Liu, Yiguo; Shi, Wenjun; Xu, Xuecai (Journal of Technical Education and Training, 2026)
With the growing emphasis on vocational education in China and the advent of the Internet of Things (IoT) and Connected and Autonomous Vehicles (CAVs), high school students, as future leaders of society, are poised to play an active role in advancing autonomous vehicle (AV) technology. To investigate the fundamental knowledge, intentions, and educational requirements of vocational high school students regarding AVs, we conducted a nationwide online questionnaire. Additionally, a Bayesian probit model was proposed to assess the final decisions of vocational high school students when deciding to participate in national college/university entrance exams and to determine whether education in AVs benefits them. The results indicate that background information, including gender, grade, speciality, and school location, is significantly correlated with participants’ final choices. As for basic cognition, application areas, and cognitive sources of AVs are significant factors for vocational high school students. In terms of intention, students’ attitudes towards AVs are closely tied to their final choice. Regarding educational needs, the content, value, methodology, and impact of AV education are crucial factors influencing vocational high school students’ final choices and should be considered key areas of focus in education. Based on the analysis results, corresponding educational strategies are proposed to improve high school students’ knowledge of AVs from the perspectives of educators, students and policymakers.